مقارنة الاتجاهات الفلسفية السائدة لدى بعض مدرسي الالعاب الفردية و الجماعية في كليات وسكول التربية البدنية وعلوم الرياضة في اقليم كوردستان _العراق - الله, جوان زرار فتح (Sulaimani Journal for Humanities, 2021)
The research aimed: - Identify the prevailing philosophical trends teaching individual games (track and field, tennis games, gymnastics, swimming) and collective (football, basketball, handball, volleyball). - recognize the differences in the prevailing philosophical trends among teachers of some individual and group games in school and colleges Physical Education and Sports Sciences in the Universities of the Kurdistan Region - Iraq. The researcher adopted the descriptive approach using the causal comparison method for its suitability with the nature of the research.. As for the research sample, they were selected from the community, which amounted to (177) teaching staff, (128) for group games and (49) for individual games. As a result of this survey, the number of the remaining sample in the research became (48) teaching by (27) for group games and (21) for individual, so the percentage of the sample to society became (33.08%). The researcher used the appropriate statistical methods to process the data, namely: percentage, the arithmetic mean, standard deviation, (T) test for non-independent and unequal samples،and smafrnof-colmenkrof. and the researcher reached conclusions, the most important of which are: - Most of the group games teachers in physical education departments and colleges in the Kurdistan Region of Iraq adopt the realistic and then existential philosophical doctrine. - Most of the individual games teachers in physical education departments and colleges in the Kurdistan Region of Iraq adopt the philosophical, existential, and then realistic direction.